Evaluasi Kinerja Pengelolaan Sampah Menurut SNI 3242 : 2008 di TPS 3R Gunung Anyar, TPS 3R Karang Pilang dan TPS 3R Kedung Cowek - Sarah Aulia; Tuhu Agung Rachmanto (Jurnal Serambi Engineering, 2024)
Due to the increasing amount of waste, the city of Surabaya has started to build several 3R TPS. However, an evaluation is still needed to assess the shortcomings of the three 3R TPS. This is to ensure that the quality improvement of the 3R TPS can be effectively implemented. The evaluation was based on 5 aspects in SNI 3242: 2008. The data collection methods used were interviews, observations and questionnaires. Based on interviews and observations, three of them have not fulfilled the institutional aspects, organisational structure sub-aspects and operational technical aspects, the processing sub-aspects have not been fulfilled by Kedung Cowek 3R TPS. Based on the questionnaire, three of them fulfil all aspects and sub-aspects. Based on the observations, TPS 3R Gunung Anyar had a production of 0.45 kg/person/day, TPS 3R Karang Pilang 0.48 kg/person/day and TPS 3R Kedung Cowek 0.57 kg/person/day. The results of the composition calculation for TPS 3R Gunung Anyar were 42.34% organic, 0.16% paper, 5.59% plastic, 4.61% other materials, 47.30% residual. For TPS 3R Karang Pilang, 53.10% organic, 2.45% paper, 4.60% plastic, 2.95% other material, 36.90% residual. Then TPS 3R Kedung Cowek 34.63% organic, 3.94% paper, 10.27% plastic, 2.87% other material, 48.29% residual.